Factors Influencing Cadre Performance in Implementing Posyandu for the Elderly: A Cross-Sectional Study - Kurniawan, Reski (Genius Journal, 2025)
Introduction: The Elderly Posyandu is a vital community-based program that supports elderly health services in Indonesia. Cadres are key actors in delivering these services, and their performance is influenced by multiple factors. Objective: This study aimed to identify the factors influencing cadre performance in implementing the Elderly Posyandu at Way Krui Health Center, Pesisir Barat Regency, in 2024. Method: A quantitative cross-sectional study was conducted in February 2025. The population consisted of 118 cadres in the Way Krui Health Center area. A total of 92 respondents were selected using the Slovin formula. Data were collected through structured questionnaires and analyzed statistically using computer software. Result: The findings revealed significant relationships between cadre performance and individual factors (ρ = 0.007), organizational factors (ρ = 0.018), psychological factors (ρ = 0.014), and leadership factors (ρ = 0.013). Cadres influenced by these factors demonstrated better performance in delivering elderly health services. Conclusion: Cadre performance in the Elderly Posyandu program is significantly affected by individual, organizational, psychological, and leadership factors. Strengthening these aspects through training, support, and effective communication is essential. Collaboration between the government, community, and health institutions is crucial to sustaining and enhancing the quality of elderly health service.